Ecotourism potentials and sustainability challenges of Gua Gajah, Merapoh, Malaysia - Elia Syarafina, Abdul Shakur; Siti Dina, Razman Pahri; Hazman, Samsudin; Akmal, Raffi; Norhayati, Ab Manaf (UKM Press, 2025)
The Pahang National Park in Malaysia is known for its impressive Mount Tahan. Gua Gajah is located in Sungai Relau National Park, Merapoh. Most tourists use the Sungai Relau trail to reach Mount Tahan in Pahang National Park for hiking and bird watching. Gua Gajah is named after the visits by elephants seeking shelter and leaving behind their droppings. The historical values, natural beauty, and rich biodiversity of Gua Gajah have made it a highly potential destination for ecotourism. This paper aims to explore the attractions of Gua Gajah and address the obstacles encountered in developing it into an ecotourism hotspot. This study adopted a qualitative approach, including document analysis, observation, and in-depth interviews. The total number of stakeholders is ten, consisting of two government officers, four community management council members, three nature guides, and one wildlife officer. This study's findings summarised that the main attraction of Gua Gajah is its natural resources of diverse flora and fauna. These valuable natural resources could become a tourist attraction and an essential livelihood source for the Merapoh villagers. The trail to Gua Gajah entails a guide leading visitors to a cave nestled amidst jungle surroundings. However, much of the trail winds through a forest, requiring further study and exploration. This study also highlighted the crucial role of the local community and the Department of Wildlife and National Parks Malaysia (PERHILITAN) cooperation in the success of this ecotourism site. These findings offer guidance for policymakers aiming to develop Gua Gajah, Pahang National Park, into an ecotourism spot that could cultivate the achievement of Sustainable Development Goals (SDG) 8 and 15. It is important to note that the findings are specific to Gua Gajah and may not apply to other ecotourism sites, each with its unique history and attractions.